The potential of management accounting and control in global operations: Profitability-driven service business development. Issue 2 (13th March 2017) - Lindholm, Anni; Laine, Teemu Juhani; Suomala, Petri
Abstract : Purpose: The purpose of this paper is to identify the financial potential of new service businesses in the context of a global machinery manufacturer. The objective is to examine the supportive role of management accounting (MA) and control in service business development, which has not been empirically examined previously. Design/methodology/approach: The paper takes advantage of an interventionist case study at a global machinery manufacturer and is empirically based on a comprehensive examination of the service business potential in the selected product category in different market areas. The researchers were actively involved in the accounting development activities underlying this paper. Findings: The results suggest that the development of a global service business is necessary to build on market area characteristics. An analysis should combine financial information and equipment fleet information across product lines and organizational units. Research limitations/implications: MA and control practices tend to require significant development to actually support the process of identifying and capturing the service business potentials. As the findings are limited to one case environment, further studies should address the longitudinal evolution of MA and control, and the choice and utilization of different performance measures, in similar contexts. Practical implications: The paper provides managerial insights on how to utilize MA information and proposes ideas for performance indicators. Originality/value: The process examined in this paper responds to the need for tools and techniques supporting service business development. MA and control could provide a comprehensive understanding of the dynamics of service business profitability potential and support in identifying and prioritizing the possible avenues of realizing such potential.